Aquisição da linguagem: as crianças e sua atitude responsiva a perguntas abertas - Jurado Filho, Lourenço Chacon [UNESP]; Zaniboni, Jéssica Santos Cardoso [UNESP] (My University, 2014)
Introduction: Since their first month of life, babies already show alternation in their communication, in which adults have an important role, assuming interaction turns with the child through questions known as eliciting questions. Verifying this alternation incited us to analyze children’s responsive attitudes toward the questions of the adult interlocutor. Objetives: (1) describe and characterize the kinds of responsive attitudes children have to open questions; (2) verify if there are any differences between the developed and non-developed kinds in the answers. Material and method: data were extracted from 28 interviews (recorded both in audio and in video) with four male children (5-6 years-old) who attended a public Kindergarten. Results: regarding the first objective, 88.7% of the attitudes were answers to the questions, 4.7% were non-responses and 6.6% were confirmation requests. Regarding the second objective, 48.2% of the answers were developed and 51.3%, non-developed. Conclusion: Although the high percentage of answers indicates that the children showed themselves sensitive to the demands of the adult interlocutor, the small percentage difference between developed and non-developed answers also indicates that children mostly depend on their assistance to develop their utterance since they oscillate between restricting themselves to the demand of the interlocutor and expanding it.

Introdução: Já em seu primeiro mês de vida, os bebês demonstram alternância na comunicação, na qual o adulto tem importante papel, assumindo turnos de interação com a criança por meio de perguntas chamadas eliciadoras. Verificar essa alternância instigou-nos a analisar atitudes responsivas de crianças para com perguntas do interlocutor adulto. Objetivos: (1) descrever e caracterizar os tipos de atitudes responsivas das crianças frente a perguntas abertas; (2) verificar se, nas respostas, há diferença entre os tipos desenvolvidos e não-desenvolvidos. Material e método: Foram extraídos dados de 28 entrevistas (registradas em áudio e em vídeo) com quatro crianças (5-6 anos) do gênero masculino que frequentavam o nível Infantil II de uma Escola Municipal de Educação Infantil. Resultados: no que se refere ao primeiro objetivo, 88,7% das atitudes foram de respostas às questões, 4,7% de não-respostas e 6,6% de pedidos de confirmação. No que se refere ao segundo objetivo, 48,2% das respostas foram desenvolvidas e 51,3% não-desenvolvidas. Conclusão: Embora o elevado percentual de respostas indique que as crianças se mostraram sensíveis às demandas do interlocutor adulto, a pequena diferença percentual entre respostas desenvolvidas e não-desenvolvidas mostra, também, que, em grande medida, as crianças dependem de seu auxílio para desenvolverem seus enunciados, já que oscilam entre restringir-se à demanda do interlocutor ou expandi-la.

Introducción: Ya en su primer mes de vida, los bebés demuestran alternancia en la comunicación, en el que el adulto tiene importante papel por asumir turnos de interacción con el niño a través de las llamadas preguntas elicitadoras. La constatación de esa alternancia de turnos nos condujo a analizar actitudes responsivas de los niños frente a preguntas del interlocutor adulto. Objetivos: (1) describir y caracterizar los tipos de actitudes responsivas de los niños ante preguntas abiertas; (2) constatar si, en las respuestas, existen diferencias entre tipos desarrollados y no desarrollados. Material y Método: Se extrajo datos de 28 entrevistas (grabadas en audio y video) con cuatro niños varones (5-6 años), alumnos del nivel Infantil II de una Escuela Municipal de Educación Infantil. Resultados: Con respecto al primer objetivo, el 88,7% de las actitudes fueron de respuesta a las preguntas; el 4,7%, de no-respuestas y el 6,6% de pedidos de confirmación. Respecto del segundo objetivo, el 48,2% de las respuestas fueron desarrolladas y el 51,3% no desarrolladas. Conclusión: Si bien el porcentaje elevado de respuestas indica que los niños se mostraron sensibles frente a los pedidos del interlocutor adulto, la pequeña diferencia porcentual entre respuestas desarrolladas y no desarrolladas señala, también, que los niños dependen en gran medida de la ayuda del adulto para desarrollar sus enunciados, dado que oscilan entre restringirse a lo solicitado por el interlocutor o a expandirlo.
Adquisición del lenguaje: los niños y su actitud responsiva a preguntas abiertas
Language acquisition: children and their responsive attitude to open questions
Keywords: Aquisição de linguagem; Perguntas abertas e fechadas; Discurso